Household barriers and facilitators to healthy eating in a U.S. census-representative sample of the general population and a low-income sample: a cross-sectional survey - Tate, Kayla E.; Bassett, Angel; Gavras, Heather; Toner, Cheryl D.; Petersen, Kristina S. (Frontiers in Public Health, 2025)
IntroductionThe present study aimed to quantify differences in barriers and facilitators to healthy eating experienced in a U.S. census-representative sample of the general population and a sample of low-income individuals.MethodsA cross-sectional survey was administered to U.S. adults. Barriers and facilitators to healthy eating were assessed with survey questions pertaining to important and influential attributes for food purchasing, attitudes about food purchasing, and barriers and facilitators to choosing healthy foods. Two samples were recruited: (1) a general sample that was census-representative for age, income, gender, and geographic region approximated from the 2022 US census data (n = 1,182); (2) a low-income sample that reported an income of less than 34,000 per year and participating in federal food or healthcare assistance programs (n = 506). Differences between samples for barriers and facilitators to healthy eating were assessed using chi-square tests for proportions.ResultsTaste and cost were identified as key barriers to healthy eating across all survey questions, and nutritional value of foods was not found to be a priority. Facilitators to healthy eating included having access to budget friendly and good tasting recipes and preparing grocery lists in advance.DiscussionFuture interventions seeking to improve diet quality may benefit from emphasizing flavor and taste as necessary components of healthy eating.